2014
DOI: 10.1186/1999-3110-55-23
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and interaction of saxicolous crustose lichens with metals

Abstract: One of the most successful mechanisms enabling fungi to survive in extreme subaerial environments is by formation of mutualistic symbioses with algae and/or cyanobacteria as lichens. Collections, field and mineral weathering studies and developments in modern instrumental and analytical techniques have considerably advanced knowledge in understanding tolerance mechanisms to stress, environmental adaptation, species concepts and evolutionary processes in lichens colonising metalliferous habitats. This review fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 70 publications
(127 reference statements)
1
14
0
Order By: Relevance
“…As lichens also take up and tolerate metals in the thallus, they are used for environmental monitoring of industrial pollution (Garty, 2001). The production of metal oxalates (e.g., hydrated copper oxalate, manganese oxalate or lead oxalate) is a common adaptive biological mechanism for metal detoxification in lichens (reviewed by Purvis, 2014). Superficial oxalates on the thallus surface may help deflect the amount of light reaching the lichen photobiont and therefore help lichens to survive in extreme environments.…”
Section: Lichen Tolerance To Toxic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…As lichens also take up and tolerate metals in the thallus, they are used for environmental monitoring of industrial pollution (Garty, 2001). The production of metal oxalates (e.g., hydrated copper oxalate, manganese oxalate or lead oxalate) is a common adaptive biological mechanism for metal detoxification in lichens (reviewed by Purvis, 2014). Superficial oxalates on the thallus surface may help deflect the amount of light reaching the lichen photobiont and therefore help lichens to survive in extreme environments.…”
Section: Lichen Tolerance To Toxic Compoundsmentioning
confidence: 99%
“…An additional detoxification response to heavy metals is found in Lecanora polytropa. Phytochelatin (cysteinerich peptides derived from glutathione) is produced to chelate these metals intracellularly (reviewed by Purvis, 2014).…”
Section: Lichen Tolerance To Toxic Compoundsmentioning
confidence: 99%
“…Crustose species, however, have the most intimate contact with their substrate, resulting in high levels of elemental accumulation [62]. Metal accumulation from the substrate in foliose and fruticose lichens is much lower and the metals are mostly restricted to the lowermost portions of thalli [63][64][65].…”
Section: Secondary Metabolite Diversity On Different Rocksmentioning
confidence: 99%
“…Fr.’ (Purvis et al . 2012, 2013; Purvis 2014) as previous investigations by Øvstedal & Lewis Smith indicated that Antarctic specimens named as A. badiofusca differed in apothecial anatomy compared with northern European specimens.
Fig. 1 A, Myriospora signyensis sampling site (yellow cross), lower slope of Manhaul Rock, 16 November 2009; B, close-up of sampling site showing Myriospora distribution (yellow box); C, field photograph showing colour variation from black, melanised to rust orange-brown and its tendency to colonize schist growing more or less perpendicular to the mineral cleavage plane; D photo-diagram of C showing the relationship between Myriospora thalli and mineral components.
…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 2)(Purvis et al 2012(Purvis et al , 2013Purvis 2014). Following the treatment byØvstedal & Lewis Smith (2001), it was provisionally named 'Acarospora cf.…”
mentioning
confidence: 99%